2014
DOI: 10.1111/cei.12332
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous antibodies against Engrailed-2 (EN2) protein in patients with prostate cancer

Abstract: SummaryWe reported the expression of the homeodomain-containing transcription factor Engrailed-2 (EN2) in prostate cancer and showed that the presence of EN2 protein in the urine was highly predictive of prostate cancer. This study aimed to determine whether patients with prostate cancer have

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Reportedly, only 20% of subjects with high PSA levels are finally diagnosed with PCa, 39–42 causing many unnecessary biopsies or treatment of individuals who do not have prostate malignancies, 43,44 and thus precise diagnosis of PCa is critical but yet remains unaccomplished. EN2 is a transcription factor involved in early embryo development of PCa and thus is only expressed in PCa cells and secreted into urine 5,45–52 . The detection of urinary EN2 is currently based on ELISA, but the sensitivity and specificity are only 66%–80% and 80%–88%, respectively 5,45–47 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reportedly, only 20% of subjects with high PSA levels are finally diagnosed with PCa, 39–42 causing many unnecessary biopsies or treatment of individuals who do not have prostate malignancies, 43,44 and thus precise diagnosis of PCa is critical but yet remains unaccomplished. EN2 is a transcription factor involved in early embryo development of PCa and thus is only expressed in PCa cells and secreted into urine 5,45–52 . The detection of urinary EN2 is currently based on ELISA, but the sensitivity and specificity are only 66%–80% and 80%–88%, respectively 5,45–47 .…”
Section: Introductionmentioning
confidence: 99%
“…EN2 is a transcription factor involved in early embryo development of PCa and thus is only expressed in PCa cells and secreted into urine. 5 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 The detection of urinary EN2 is currently based on ELISA, but the sensitivity and specificity are only 66%–80% and 80%–88%, respectively. 5 , 45 , 46 , 47 This study has demonstrated that the 3p3 immunoassay shows superior sensitivity and specificity in the urinary EN2 detection of PCa patients—no false‐negative signals for PCa patients (100% sensitivity) and no false‐positive signals for other prostate‐related diseases (BPH and BCa) and healthy controls (100% specificity)—indicating that this innovative approach is highly suitable as a novel immunoassay platform for simple urine test‐based, clinical in vitro cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation